2015
DOI: 10.1371/journal.pgen.1005468
|View full text |Cite
|
Sign up to set email alerts
|

Three Different Pathways Prevent Chromosome Segregation in the Presence of DNA Damage or Replication Stress in Budding Yeast

Abstract: A surveillance mechanism, the S phase checkpoint, blocks progression into mitosis in response to DNA damage and replication stress. Segregation of damaged or incompletely replicated chromosomes results in genomic instability. In humans, the S phase checkpoint has been shown to constitute an anti-cancer barrier. Inhibition of mitotic cyclin dependent kinase (M-CDK) activity by Wee1 kinases is critical to block mitosis in some organisms. However, such mechanism is dispensable in the response to genotoxic stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 76 publications
1
47
0
Order By: Relevance
“…1). Deletion of the Mec1/ATR effector Swe1/Wee1 (Palou et al 2015) made no difference.
Fig. 1Deletion of Mec1 is not sufficient to allow the segregation of damaged chromosomes.
…”
Section: Chromosome Segregation In Response To Genotoxic Stress Is Stmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Deletion of the Mec1/ATR effector Swe1/Wee1 (Palou et al 2015) made no difference.
Fig. 1Deletion of Mec1 is not sufficient to allow the segregation of damaged chromosomes.
…”
Section: Chromosome Segregation In Response To Genotoxic Stress Is Stmentioning
confidence: 99%
“…In our recent work to better understand how cells block anaphase in response to challenged DNA replication, we showed that the S phase checkpoint prevents chromosome segregation through three independent, redundant, downstream pathways (Palou et al 2015). Mec1/ATR inhibits mitotic Cdk1 activity through downstream effector kinases, Rad53/Chk2 and Swe1/Wee1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclin Dependent Kinase (CDK) activity is under strict checkpoint regulation upon different genotoxic stresses (Hartwell & Weinert 1989; Furnari et al . 1997; Palou et al . 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Early work in mitotic cells indicated that Swe1-catalyzed Cdk1 phosphorylation regulates the morphogenesis checkpoint (Lew and Reed 1995). However, it is now known that Swe1 is also a component of one of three Mec1-dependent mechanisms that operate in the S phase checkpoint to prevent cell cycle progression into mitosis (Palou et al 2015). …”
mentioning
confidence: 99%